Synthesis of 2,5-Disubstituted Oxazoles from Arylacetylenes and α-Amino Acids through an I2/Cu(NO3)2•3H2O-Assisted Domino Sequence - Wang, Jungang; Cheng, Yan; Xiang, Jiachen; Wu, Anxin (Synlett, 2019)
A new strategy has been developed for the synthesis of 2,5-disubstituted oxazoles from easily available arylacetylenes and α-amino acids in the presence of Cu(NO3)2•3H2O and iodine. This reaction process involves the I2/Cu(NO3)2•3H2O-assisted transformation of arylacetylene to α-iodo acetophenone, Kornblum oxidation to phenylglyoxal, condensation to imine, decarboxylation/annulation/oxidation reaction sequence to approach 2,5-disubstituted oxazoles.
Keywords: oxazoles; α-amino acids; copper catalysis; cascade reactions; alkynes